(untitled) (Bangladesh Journal of Medicine, 2020)
Primary cardiac tumor are extremely rare. Incidence is approximately 0.017-0.019% of all primarytumor. An early diagnosis of cardiac tumor may improve the outcome. Bangladesh J Medicine July 2020; 31(2) : 111-113